2021
DOI: 10.1042/bsr20181627
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of lncRNA DANCR expression in human cancers: a systematic review and meta-analysis

Abstract: Background: Several studies demonstrated that long non-coding RNA differentiation antagonizing non-protein coding RNA (lncRNA DANCR) expression might have the potential capacity to predict the cancer prognosis, however, definite conclusion has not been obtained. The aim of this meta-analysis was to evaluate the prognostic value of lncRNA DANCR expression in cancers. Methods: PubMed, Web of Science, Scopus and Embase were comprehensively searched for relevant studies. Studies meeting all inclusion standards wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…We attempted to use mRNA data, LncRNA data and clinical follow-up data from the tumor genome atlas to identify LncRNA related to GBM prognosis and provide potential therapeutic targets for treatment. lncRNAs have become novel biomarkers for the diagnosis and prognosis of various human cancers [33][34][35][36]. We speculated that the differential expression of lncRNAs might be used as biomarkers to determine the prognosis of GBM patients, and previous studies have shown that several lncRNAs, including MEG3, H19 and Gas5, are abnormally expressed in all GBM patients [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…We attempted to use mRNA data, LncRNA data and clinical follow-up data from the tumor genome atlas to identify LncRNA related to GBM prognosis and provide potential therapeutic targets for treatment. lncRNAs have become novel biomarkers for the diagnosis and prognosis of various human cancers [33][34][35][36]. We speculated that the differential expression of lncRNAs might be used as biomarkers to determine the prognosis of GBM patients, and previous studies have shown that several lncRNAs, including MEG3, H19 and Gas5, are abnormally expressed in all GBM patients [37][38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…SNHG13, a lncRNA also known as differentiation antagonizing non-protein coding RNA (DANCR), plays a regulatory role as an oncogene in multiple human cancers. DANCR expression is correlated with pathogenesis and progression and is predictive of the outcome of several neoplasms (38,39). PCa studies have indicated that DANCR may affect the treatment response to chemotherapy.…”
Section: Lncrna Snhgs In Prostate Cancermentioning
confidence: 99%
“…Long non-coding RNAs (LncRNAs) represent the prevalent types of RNA molecules, typically exceeding 200 bp in size 32 ; 33 . Although they are unable to encode proteins, accumulating evidence has highlighted their critical role in regulating immune responses against cancer 32 ; 34 ; 35 . Through their functions, lncRNAs have signi cantly contributed to elucidating the complex molecular pathways that underlie cancer immunity and could be employed as novel therapeutic targets for cancer immunotherapy [36][37][38] .…”
Section: Introductionmentioning
confidence: 99%